Zoonotic Ectoparasite Burden in House Rats (Rattus spp.) in Selected Urban and Rural Areas of NCR and CALABARZON - Chan, Helenar; Flores, Mary Jane; Maghirang, Eligio Santiago; Arellano, Bridget; Chan, Jan Michael (Universitas Airlangga, 2024)
Rats and other mammalian species co-inhabiting or living in proximity with humans can serve as potential reservoir hosts and may contribute to the transmission of parasitic infections. Aside from endoparasites, ectoparasites such as lice, mites, ticks, and fleas, can also serve as vectors of various pathogens inducing diseases and contaminating the environment. This study aimed to determine the prevalence rate of Polyplax spinulosa (spiny rat louse) infestation among house rats in selected urban and rural areas in the Philippines. A total of 60 Rattus spp. were captured and examined. The overall prevalence rate of Polyplax spinulosa was 71.7% (43/60). Of the infestations, 23.3% (14/60) were recorded in Metro Manila while 48.3% (29/60) were recorded in CALABARZON. These results have revealed that rodents like rats play an important role in both direct and indirect transmission of zoonotic diseases since these pests themselves could be host to a variety of diseases. As a result, there is an immediate need to provide education and raise awareness about the role of rodents as reservoir hosts and vectors of these zoonotic diseases to develop long-term strategies for controlling and preventing rodent populations and the transmission of zoonotic ectoparasite infestation.